Nasopharyngeal colonization dynamics with Streptococcus pneumoniae and associated antimicrobial resistance in a South African birth cohort - Manenzhe, Rendani Innocent (Department of Pathology, 2020)
Introduction: Nasopharyngeal (NP) colonization by Streptococcus pneumoniae (the pneumococcus) precedes the development of respiratory tract infection. Colonization by antimicrobial-resistant pneumococci, especially in infants, is a major public health concern as pneumococcus is a frequent cause of bacterial acute respiratory tract infections among children. This study longitudinally investigated antimicrobial resistance amongst pneumococci colonizing the nasopharynx of South African infants immunized with the 13- valent pneumococcal conjugate vaccine (PCV13). Furthermore, the study explored strainlevel pneumococcal colonization patterns and associated antimicrobial resistance determinants as well as the composition of the NP antibiotic resistome using shotgun metagenomic sequencing. Methods: NP swabs were collected every second week from birth through the first year of life from 137 infants who were immunized with 2+1 doses of PCV13. These were the first 137 infants enrolled in the cohort who had the most complete fortnightly NP sampling (defined as at least 23-26 fortnightly collected NP swabs). Pneumococci were identified and serotyped using conventional techniques, and their antibiotic susceptibility profiles determined by disc diffusion and E-test. A subset of 196 NP samples from 23 infants were selected based on changes in serotype or antimicrobial resistance. These were subjected to broth enrichment, total nucleic acid extraction and subsequent shotgun metagenomic sequencing. Sequence reads were assembled and aligned to reference pneumococcal genomes. In-silico pneumococcal capsular, multilocus sequence typing, and antimicrobial resistance determinants were described. Finally, antibiotic resistance genes were identified from all bacterial contigs, to determine the NP resistome. Results: 1520 pneumococcal (760 non-duplicate) isolates were recovered from 137 infants; including non-typeable (n = 99), PCV13 (n = 133), and non-PCV13 serotypes (n = 528). The prevalence of penicillin, erythromycin, and cotrimoxazole non-susceptibility was 19% (147/760; 95% CI 17-22%) (3% resistant), 18% (136/760; 95% CI 15-21%) (14% resistant) and 45% (344/760; 95% CI 42-49%) (36% resistant), respectively. The predominant penicillin-non-susceptible serotypes included 15B/15C (n = 20), 19A (n = 13), 15A (n = 10), 19F (n = 8), and 21 (n = 8). Multi-drug resistance (MDR) was observed in 9% (68/760; 95% CI 7-11%) of the isolates. PCV13 serotypes were more likely to be non-susceptible, compared to non-PCV13 serotypes, to penicillin (26% vs. 16%, p = 0.007), erythromycin (23% vs. 15%, p = 0.027) and cotrimoxazole (62% vs. 41%, p < 0.001). Non-susceptibility to penicillin, erythromycin, and cotrimoxazole remained relatively constant through the first year of life (X 2 test for trend: p = 0.184, range 0 – 25%; p = 0.171, range 0 – 27%; and p = 0.572, range 0 – 55%, respectively). Overall, penicillin or erythromycin-non-susceptible pneumococci were carried for a shorter duration than susceptible pneumococci (penicillin [mean days, 18 vs. 21, p = 0.013] and erythromycin [mean days, 18 vs. 21, p = 0.035]). Forty-five percentage (61/137) of infants carried the same serotype which acquired or lost resistance over time, and these changes were predominantly for penicillin (76%, 79/104). Of the 196 NP samples sequenced, 174 had corresponding positive cultures for pneumococci and, of these, 152 were assigned an in-silico serotype. Metagenomic sequencing detected a single pneumococcal serotype in 85% (129/152), and co-colonization in 15% (23/152) of NP samples, respectively. In total, 22 different pneumococcal serotypes were identified, with 15B/15C (n = 49) and 16F (n = 21) being the most common non-PCV13 serotypes, while 23F (n = 9) and 19A (n = 8) were the most common PCV13 serotypes. Twenty-six different sequence types (STs), including 4 novel STs were identified. Mutations in the folA and folP genes, associated with cotrimoxazole resistance, were detected in 89% (87/98) of cotrimoxazole-non-susceptible pneumococci and mutations in the pbp1a and pbp2x genes, known to confer beta-lactam resistance, were identified in penicillin nonsusceptible ST705215B/15C isolates. A total of 329 antimicrobial resistance (AMR) genes were detected in 64% (125/196) of the sequenced samples, including 36 non-redundant genes ranging from 1 to 14 genes per sample. The predominant AMR genes detected were those conferring resistance to beta-lactams (52%, 172/329), macrolide-lincosamide-streptogramin (17%, 56/329), and tetracycline (12%, 38/329). The msrD, ermB, and mefA genes were only detected from pneumococcal reads. The predominant resistance genes detected from nonpneumococcal reads included blaOXA-60, blaOXA-22, and blaBRO-1. Conclusion: NP carriage of antibiotic-non-susceptible pneumococci was relatively constant throughout the first year of life. Despite high vaccine coverage levels, PCV13 serotypes were identified and were more commonly non-susceptible to penicillin, erythromycin, and cotrimoxazole. Overall, penicillin or erythromycin-non-susceptible pneumococci were carried for a shorter duration than susceptible pneumococci, however, non-susceptible PCV13 serotypes were carried for a longer duration than non-susceptible non-PCV13 serotypes. Direct shotgun sequencing from enriched NP samples was shown to be a powerful technique for a detailed description of the pneumococcal component of the NP microbiome and resistome, and its use should be explored similarly for other bacteria in this niche.